Cyclograpsus H. Milne Edwards 1837 - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
Genus Cyclograpsus H. Milne Edwards, 1837 Type species. Cyclograpsus punctatus H. Milne Edwards, 1837 [Type locality: Indian Ocean]. Remarks. Only one species in the western Atlantic (see below). Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 104, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155